Colombia : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
Colombia's economy has been resilient to the adverse global shocks of recent years. Inflation has been subdued, credit growth has eased, and financial soundness indicators are strong. The strong balance of payments continues to put upward pressure on the Colombian peso. In 2013, growth is expected to rise and inflation to remain on target. Short-term risks to the outlook continue to be tilted to the downside. The central bank's intervention policy is geared at containing exchange rate volatility and strengthening external buffers.